Hydropower and irrigation development: implications for water resources in the Nam Ngum River of the Mekong Basin. [Abstract only]. - Lacombe, Guillaume; Douangsavanh, Somphasith; Baker, J.; Hoanh, Chu Thai; Bartlett, R.; Phongpachith, C.; Jeuland, M. (2013)
To meet rising demands for food and energy, the number of hydropower dams is growing rapidly and irrigation schemes will likely expand, in the Mekong Basin. The cumulative hydrological effect of planned water resources development has previously been assessed at the Mekong Basin scale. This paper analyzes how water control structures modify the balance between water demand and water supply along the Nam Ngum River, a Mekong tributary in Lao PDR. The Nam Ngum Basin, already containing both irrigation schemes and hydropower dams, has the potential for significantly enlarged river-fed irrigation, as well as additional upstream hydropower dams. We analyzed flow data recorded since 1962, in combination with a reservoir system optimization model, to assess changes in monthly river flows induced by existing and planned hydropower dams. Current and potential irrigation water demands were assessed from satellite images, cropping calendars and simple crop water balance. Our results indicate that, by the 2030s, if eight hydropower dams are completed in the Nam Ngum Basin, dry season river flow could increase by more than 200% and wet season flows could decrease by 20%. In the absence of dam storage, current irrigation water demand would compete with minimum environmental flow requirements during dry years. In contrast, full hydropower development allows current irrigation water demand to triple, to reach the potential levels of development, whilst maintaining environmental flows. The contribution of the Nam Ngum Basin to the Mekong River flow at Kratie, a few hundreds kilometers upstream of the Tonle Sap Lake, has changed from 5 to 15% in April, since hydropower dams started developing in the Mekong Basin, suggesting that the effect of water control development in the Nam Ngum Basin impacts water resources further downstream. Beyond the effects on water resources, there are a number of other impacts on fisheries, sediment, biodiversity, ecosystems, and population resettlement that should be considered in order to better understand the environmental and socioeconomic costs and benefits of these hydropower dams.